Dialectical behavior therapy skills use and emotion dysregulation in personality disorders and psychopathy: a community self-report study. Issue 1 (December 2016) - Neacsiu, Andrada; Tkachuck, Mathew
Abstract Background Emotion dysregulation is a critical transdiagnostic mental health problem that needs to be further examined in personality disorders (PDs). The current study examined dialectical behavior therapy (DBT) skills use, emotion dysregulation, and dysfunctional coping among adults who endorsed symptoms of cluster B PDs and psychopathy. We hypothesized that skills taught in DBT and emotion dysregulation are useful for adults with PDs other than borderline personality disorder (BPD). Methods Using a self-report questionnaire, we examined these constructs in three groups of community adults: those who reported symptoms consistent with borderline personality disorder (BPD;N =  29), those who reported symptoms consistent with any other cluster B PD (N  = 22), and those with no reported cluster B PD symptoms (N  = 77) as measured by the Personality Diagnostic Questionnaire-4 + . Results Both PD groups reported higher emotion dysregulation and dysfunctional coping when compared to the no PD group. Only the BPD group had significantly lower DBT skills use. DBT skills use was found to be a significant predictor of cluster B psychopathology but only before accounting for emotion dysregulation. When added to the regression model, emotion dysregulation was found to be a significant predictor of cluster B psychopathology but DBT skills use no longer had a significant effect. Across all groups, DBT skills use deficits and maladaptive coping, but not emotion dysregulation, predicted different facets of psychopathy. Conclusion Emotion dysregulation and use of maladaptive coping are problems in cluster B PDs, outside of BPD, but not in psychopathy. Inability to use DBT skills may be unique to BPD. Because this study relied exclusively on self-report, this data is preliminary and warrants further investigation.